Modulation of the nociceptive withdrawal reflex in walking is not changed by the presence of tonic pain - Joanna Reeves; Connor Thacker; Geoffrey Cunningham; Sam Hughes; Jennifer L. Davies (Experimental Brain Research, 2026)
Tonic pain inhibits the nociceptive withdrawal reflex (NWR). NWR magnitude varies across the gait cycle, but it is unknown whether tonic pain affects this phase-dependent modulation of the NWR during walking. Sixteen healthy participants (mean ± SD age: 29 ± 9 years, 3 males) walked on a treadmill with and without tonic pain applied to the left arm. Lower-limb kinematics and electromyography (EMG) from bilateral biceps femoris, vastus lateralis, soleus and tibialis anterior were recorded. At predefined points in the gait cycle, a brief electrical stimulus was applied to the arch of the right foot to elicit an NWR. Reflex responses were calculated from the EMG as a percentage difference to the EMG present without any stimulation. There was a significant effect of gait phase on reflex response in all muscles except ipsilateral biceps femoris. When accounting for the intensity of tonic pain, there was a 0.64 decrease in normalised reflex response in the contralateral tibialis anterior with tonic pain versus control ( p = 0.009). There were no other effects of tonic pain on reflex response ( p > 0.05). There was an increase in knee flexion on the stimulated leg when it was unloading, however there was large variability in the kinematics. Stimulation during loading response saw around a 3° increase ( p = 0.007) in dorsiflexion in the contralateral leg. Our findings suggest that tonic pain does not influence the modulation of the NWR during walking. We propose that the need to maintain balance overrides any effects of endogenous pain modulation.